Penggunaan Media Gambar dalam Meningkatkan Kemampuan Membaca Permulaan pada TK PGRI Jatisela - Siti Hajar (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: The Use of Image Media in Improving Initial Reading Ability at Jatisela PGRI Kindergarten]. This study aims to determine the extent to which the use of image media can improve the initial reading ability in Group B of the Jatisela PGRI Kindergarten Students in the 2017/2018 Academic Year. This study is a Classroom Action Research with qualitative-quantitative data analysis techniques. The subjects of the study were 23 students of group B of the Jatisela PGRI Kindergarten. The results of data analysis show that the use of image media can (1) improve students’ initial reading ability, (2) make learning activities more active and fun, (3) the students’ initial reading ability after the second cycle increases with a percentage of 95.65%. Based on the results of the study it can be concluded that the use of image media can improve the students’ initial reading ability of group B Jatisela PGRI Kindergarten Sesela Village, Gunungsari, West Lombok 2017/2018 Academic Year.